2020
DOI: 10.1128/jb.00128-20
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Fatty Acids Remodel Staphylococcus aureus Lipid Composition through Fatty Acid Kinase

Abstract: Staphylococcus aureus can utilize exogenous fatty acids for phospholipid synthesis. The fatty acid kinase FakA is essential for this utilization by phosphorylating exogenous fatty acids for incorporation into lipids. How FakA impacts the lipid membrane composition is unknown. In this study, we used mass spectrometry to determine the membrane lipid composition and properties of S. aureus in the absence of fakA. We found the fakA mutant to have increased abundance of lipids containing longer acyl chains. Since S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
45
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 60 publications
11
45
1
Order By: Relevance
“…This observation implies that de novo BCFA synthesis is predominant during infection and potentially limits bacterial acquisition of UFA. This notion is supported by previous studies indicating that culture of WT S. aureus in the presence of oleic acid (18:1) does not appreciably change BCFA content, as approximately 50% of membrane is still composed of BCFA [11,62]. Furthermore, the sn-2 position of S. aureus phospholipid is exclusively occupied by BCFA in most conditions, implying an established preference for BCFA [9,16,20].…”
Section: Plos Pathogenssupporting
confidence: 75%
“…This observation implies that de novo BCFA synthesis is predominant during infection and potentially limits bacterial acquisition of UFA. This notion is supported by previous studies indicating that culture of WT S. aureus in the presence of oleic acid (18:1) does not appreciably change BCFA content, as approximately 50% of membrane is still composed of BCFA [11,62]. Furthermore, the sn-2 position of S. aureus phospholipid is exclusively occupied by BCFA in most conditions, implying an established preference for BCFA [9,16,20].…”
Section: Plos Pathogenssupporting
confidence: 75%
“…Figure S4 fatty acids were elongated prior to incorporation into diacylglycerolipids. Elongation of exogenously supplemented unsaturated fatty acids has also been observed previously (16,36).…”
Section: Figsupporting
confidence: 56%
“…S3 in the supplemental material) and that SCUFAs can undergo elongation within S. aureus (Fig. S4), suggesting that host-derived fatty acids can fully participate in all fatty acid (FASII) and glycerolipid metabolic pathways (16,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent literature citations associated with the emergence of MRSA have reported numerous investigations which had focused on the role of Atorvastatin in combating these hardy virulent MRSA strains (Pruefer Diethard et al, 1999;Adhikari and Novick, 2005;Liu et al, 2005Liu et al, , 2008;DeMars et al, 2020;Wang et al, 2020). Recently it has also been found that statins may have a positive role in treating the symptoms of Coronavirus COVID-19 which is caused by SARS Cov-2 virus.…”
Section: Discussionmentioning
confidence: 99%